Reconfiguring Ottoman Gender Boundaries and Sexual Categories by the mid-19th century - Özgören Kinli, İrem (Política y Sociedad, 2013)
This research extends the theory of the civilizing process of Norbert Elias to the gender issue in the Ottoman Empire and thereby in some respects provides a test of his original theory. This study is based on the assumption that the conscious policy of the Ottoman modernization by the ruling elite exhibited many symptoms resembling those of the European civilizing process. The socio-historical process of bureaucratization of the Ottoman state fostered the changes in manners and forms of cultural expression which brought with it the advance of the threshold of shame and embarrassment in gender relations during this process. Drawing on this assumption, the article looks at the changes in the way people control themselves and others in the expression of their impulses and emotions. In turn, - the question of how the margins of tolerance in sexual matters and in the expression of emotions and desires changed during this civilizing process - formulates the major concern of this paper. Since manuals on etiquette, manners books, diaries and archives are the richest sources for this purpose, this project employs the analysis of these cultural texts, in order to make inferences from the cultural transformations within the Ottoman Empire. The research hopes to offer new perspectives in reorienting the way we look at the development of the Ottoman culture within the context of figurational sociology.